1984
DOI: 10.1021/bi00297a008
|View full text |Cite
|
Sign up to set email alerts
|

Subunit binding in the pyruvate dehydrogenase complex from bovine kidney and heart

Abstract: Binding of pyruvate dehydrogenase (E1) and dihydrolipoamide dehydrogenase (E3) to the isolated dihydrolipoamide acetyltransferase (E2) core of the pyruvate dehydrogenase complex from bovine heart and kidney was investigated with equilibrium, competitive binding, and kinetic methods. E2, which consists of 60 subunits arranged with icosahedral 532 symmetry, apparently possesses six equivalent, noninteracting binding sites for E3 dimers. It is proposed that each E3 dimer extends across 2 of the 12 faces of the E2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…The earlier studies demonstrated a greater affinity of the active E1 form to the E2 sites compared with the phosphorylated form (38,46). Our results are in support of these findings and suggest that amino acid substituted mutants of site 1 can not easily replace the wild-type E1 when interacting with E2 (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…The earlier studies demonstrated a greater affinity of the active E1 form to the E2 sites compared with the phosphorylated form (38,46). Our results are in support of these findings and suggest that amino acid substituted mutants of site 1 can not easily replace the wild-type E1 when interacting with E2 (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…A greater affinity of the active non-phosphorylated form of the dehydrogenase (El) component for the E2 core has also been reported for pyruvate dehydrogenase complex (Pratt et al, 1979;Wu & Reed, 1984). The results here indicate this may also be true of branched-chain 2-oxo acid dehydrogenase complex.…”
Section: Discussionsupporting
confidence: 72%
“…From D20,w = RT(S20,wAfr(l -vp20,w) and eq 3, an rH = 23.0 nm is calculated for both complexes. Our best estimate of M, of our kidney preparations is 7.5 X 106 based on the assumption that there are 60 E2 subunits and of studies to estimate the level of each of the other components: E1, Cate et al (1979); E3, Wu and Reed (1984); and kinase, Rahmatuallah et al (1987); protein X, Jilka et al (1986). Our preparations of kidney complex give an S°20vl of 73.…”
mentioning
confidence: 85%